# maths

posted by .

If y=x+tanx then prove that cos^2x(y2)-2y+2x=0 where y2 is the second derivative...plz help me out.

• maths -

y=x+tan(x)
y'=1+sec(x)^2
y"=0+2sec(x)*(-1/cos²(x))(-sin(x))
=sec²(x)tan(x)

=>
cos²(x)y"-2y+2x
=2cos²(x)sec²(x)tan(x)-2(x+tan(x)+2x
=2tan(x)-2x-2tan(x)+2x
=0

• maths -

y"=0+2sec(x)*(-1/cos²(x))(-sin(x))
=2sec²(x)tan(x)

## Similar Questions

1. ### Math

1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not …
2. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
3. ### Pre-Calc

How do I solve this? My work has led me to a dead end. tan(45-x) + cot(45-x) =4 my work: (tan45 - tanx)/(1+ tan45tanx) + (cot45 - cotx)/(1 + cot45cotx) = 4 (1-tanx)/(1+tanx) + (1-cotx)/(1+cotx) = 4 Then I found a common denominator,
4. ### Mathematics - Trigonometric Identities

Prove: sinx + tanx = tanx (1 + cosx) What I have so far: LS: = sinx + tanx = sinx + (sinx / cosx) = (sinx) (cosx) + sinx / cos = tanx (cosx + sinx) I don't know what to do now
5. ### Math

find the second derivative of ln(sinx) i worked this out and i got -tanx
6. ### maths - trigonometry

I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the second. …
7. ### Math

Prove each of the following identities. a)tan^2x = 1 – cos^2x/cos^2x b)sinx/1 – sin^2x = tanx/cosx
8. ### Math

Derivative of y=sec(tanx)? I don't get how it is secxsecx*secxtanx*tanxtanx. Where does an extra tanx come from?
9. ### trigonomentry out of ideal help ah!crying

compute.. Cos(1degree)+cos(3degree)+cos(5degree)+...+Cos(179degree) plz show working even an hint can,t help me.Have been do maths alday my brain is fried..Ah thanks
10. ### trig prove plz anyone help

Prove that: x - tan^-1(x) = tan^-1{(tanx - x)/(xtanx + 1)} plz help

More Similar Questions